CLASSIFICATION OF THREATS TO STATE INFORMATIVE RESOURCES OF TECHNICAL DIRECTION. METHODOLOGY OF CONSTRUCTION OF CLASSIFIER - Юдін, О. К.; Бучик, С. С. (Science-based technologies, 2015)
In the article the continued subjects of construction of classifier of threats to the state informative resources, methodology of construction of which by authors was offered before. Some modern theoretical and practical approaches to the decision of normatively-legal, organizational and technical tasks for realization of the process of defence of the state informative resources are the objects of research in the previous works . The conducted analysis of publications on the subjects of the article shows that the considerable attention was always paid for research of technical direction of defence of informative resources, but in the classifier of threats offered by authors the technical aspiration was not distinguished in the separate phenomenon. Certain threats of technical aspiration and an example of their classification is made. The result of the further improvement and expansion of methodology of construction of classifier of threats of the state informative resources is the development of classifier of next wide class of threats – threats of technical aspiration. Completion of creation of classifier of threats is carried out to the state informative resources, which on the whole contains the threats of normatively-legal, organizational and technical aspiration.